2012
DOI: 10.2337/db11-1154
|View full text |Cite
|
Sign up to set email alerts
|

Loss of HGF/c-Met Signaling in Pancreatic β-Cells Leads to Incomplete Maternal β-Cell Adaptation and Gestational Diabetes Mellitus

Abstract: Hepatocyte growth factor (HGF) is a mitogen and insulinotropic agent for the β-cell. However, whether HGF/c-Met has a role in maternal β-cell adaptation during pregnancy is unknown. To address this issue, we characterized glucose and β-cell homeostasis in pregnant mice lacking c-Met in the pancreas (PancMet KO mice). Circulating HGF and islet c-Met and HGF expression were increased in pregnant mice. Importantly, PancMet KO mice displayed decreased β-cell replication and increased β-cell apoptosis at gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 56 publications
3
119
0
1
Order By: Relevance
“…Since the rate of β cell proliferation is strongly influenced by the metabolic environment of the host (14)(15)(16), in some cases trumping islet-intrinsic factors (17,18), the working model in the field has been that circulating factors regulate β cell proliferation. Many different signals have been proposed to drive β cell proliferation in response to insulin demand, principally nutrients (14,15,19,20) and growth factors (8,(21)(22)(23). However, no circulating signal explains all the observations, and models in which a distant organ senses insulin demand and directs β cells to proliferate are complicated and indirect.…”
Section: Introductionmentioning
confidence: 99%
“…Since the rate of β cell proliferation is strongly influenced by the metabolic environment of the host (14)(15)(16), in some cases trumping islet-intrinsic factors (17,18), the working model in the field has been that circulating factors regulate β cell proliferation. Many different signals have been proposed to drive β cell proliferation in response to insulin demand, principally nutrients (14,15,19,20) and growth factors (8,(21)(22)(23). However, no circulating signal explains all the observations, and models in which a distant organ senses insulin demand and directs β cells to proliferate are complicated and indirect.…”
Section: Introductionmentioning
confidence: 99%
“…Islet β-cell adaptive responses occur after placentation and are rapidly reversed post-partum, consistent with placental signals playing a major role in informing β-cells of the gestational stage via circulating mediators. It is well established that the placental lactogens and prolactin play important roles in metabolic adaptations during pregnancy, but these cannot account for all of the β-cell adaptive responses because the time-course of elevations in their circulating levels does not match that of increases in β-cell mass [7-11]. The current study aimed to identify other placentally-derived mediators with the potential to influence β-cells to facilitate future functional studies into changes in the endocrine capacity of islets in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The insufficient compensation of insulin secretion contributes to the development of gestational diabetes. Meanwhile, numerous studies performed in pregnant mice have shown that proliferation of b cells is augmented in response to pregnancy (Zhang et al 2010, Demirci et al 2012, Jacovetti et al 2012. The prolactin receptor is the target of prolactin and placental lactogen, and is expressed in pancreatic b cells to contribute for augmentation of insulin release during pregnancy (Buchanan & Xiang 2005).…”
Section: Discussionmentioning
confidence: 99%